2010
DOI: 10.1021/jf102408y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Chemical and Biochemical Properties of Different Melon Cultivars: Standard, Hybrid, and Grafted Melons

Abstract: Chemical and biochemical properties of standard, hybrid, and grafted melons cultivated under the same agricultural conditions in adjacent fields in the Cumra region of Turkey were investigated and compared based on pH, Brix, antioxidant activity, total phenolics, ascorbic acid, individual phenolics, sugar, and organic acid values. Seventeen different phenolic constituents were quantified by reverse phase high-performance liquid chromatography (RP-HPLC). The highest phenolic acid variability and content were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 18 publications
7
51
0
4
Order By: Relevance
“…We found that the pulp samples stored under refrigeration presented the lowest SS/TA ratios for the three fruit colors. The SS/TA ratio is considered one of the best ways to assess the palatability of fruits, with acidity being decisive in this respect, since higher acidity reduces the ratio (Kolayli et al, 2010;Tietel et al, 2010). The results obtained indicate that from the physico-chemical standpoint, all the passion fruit pulp samples, both from the fresh fruit and those kept in cold storage, presented pH, soluble solids and titratable acidity values within the technical regulations for standards of identity and quality for passion fruit pulp issued by the Brazilian Ministry of Agriculture, which establishes pH between 2.70-3.80, soluble solids greater than 11 ºBrix and titratable acidity above 2.50%.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the pulp samples stored under refrigeration presented the lowest SS/TA ratios for the three fruit colors. The SS/TA ratio is considered one of the best ways to assess the palatability of fruits, with acidity being decisive in this respect, since higher acidity reduces the ratio (Kolayli et al, 2010;Tietel et al, 2010). The results obtained indicate that from the physico-chemical standpoint, all the passion fruit pulp samples, both from the fresh fruit and those kept in cold storage, presented pH, soluble solids and titratable acidity values within the technical regulations for standards of identity and quality for passion fruit pulp issued by the Brazilian Ministry of Agriculture, which establishes pH between 2.70-3.80, soluble solids greater than 11 ºBrix and titratable acidity above 2.50%.…”
Section: Resultsmentioning
confidence: 99%
“…This melon group has the highest ascorbic acid, sweetness and sugar content. The immature fruits of the Cinikiz melon have a light green skin color with dark green spots; mature fruits, a yellow colored skin [16,18]. Individual plants of the Hasanbey or Cinikiz melon genotypes under in vitro conditions develop organs of similar size due to the elimination of environmental conditions and are, genetically controlled.…”
Section: Two Important Turkish Melon Cultivars: Hasanbey and Cinikizmentioning
confidence: 99%
“…Due to climatic conditions, melon harvesting in Turkey can change based on cultivation regions, but generally it is done from June to September [18]. …”
Section: The Importance Of Melon Production In Turkeymentioning
confidence: 99%
See 2 more Smart Citations